Ghrelin and Obestatin Levels as a Novel Marker in Iraqi Obese Children (Baghdad Science Journal, 2023)
Obesity is an escalating health problem in developing countries. One to ten children worldwide are overweight in a report showed by the International Obesity Task Force. Ghrelin, orexigenic peptide, has 28 amino acids, it is considered the greatest remarkable promotion in the last two decades for understanding the physiological changes of action regulating food intake and hunger. Obestatin is a 23-amino acid peptide nearly connected to ghrelin that secures from substitution splicing the alike resort molecule, pre-proghrelin. The study is designed to assess the level of ghrelin and obestatin in Iraqi obese children and its relation with other biochemical parameters. Ghrelin and obeststin levels were measured in sixty obese children; the range of their age was (5-16) years, and this group was compared to 30 children in a healthy state as a control. Serum FBS, PPBS, and also lipid profiles (TG, TC, HDL-c, and LDL-c) were determined in the studied groups. Calculation of insulin resistance was done by using (HOMA-IR) a Homeostasis Model assessment of insulin resistance. Ghrelin levels were lower in a significant way in subjects who have obesity in comparison with control group.  Significantly, there was a high increase in obestatin in obese patients when compared with control. This study demonstrates that obestatin raises and ghrelin is low in obesity, these hormones are related to the resistance of insulin, and there is an association between ghrelin and oxidative stress. The scales between obestatin and ghrelin are likely disturbed in obesity.